Integration and the regions of Europe : how the right policies can prevent polarization - Braunerhjelm, P.; Braunerhjelm, Pontus; Centre for Economic Policy Research (Great Britain) (London : Centre for Economic Policy Research, 2000)
This report analyses how the geographic pattern of production and employment in Europe will be affected by market integration, increased direct investment, more mobile financial capital and a sharper, global division of labour.
"February 2000"--T.p. verso.
Includes bibliographical references (p. 105-115).
osc 2/9/16
Loans
Keywords: Regional Integration; International economic integration; Europe; European Union countries